‘Initiative-Decision’ Typology of New Product Launching (NPL) into Local Market: Toward Interaction Mechanism - Firmanzah, Firmanzah (UI Scholars Hub, 2021)
New product launching (NPL) process in subsidiaries is very complex, expensive and risky. This process is marked by the problem of role partition between headquarter and subsidiaries. This research emphasizes the quality of relation between subsidiaries and headquarter which determines the qualities of NPL process into local market. Typology of initiative-decision during NPL process has been documented. Using cluster analysis, three clusters of ‘initiative-decision’ during NPL are found in this research: ‘headquarters domination’, ‘mix-initiative’ and ‘interaction’. Using ANOVA analysis, this research found that interaction between subsidiary and headquarter managers positively increases the effectiveness of marketing-strategy during NPL process. This finding suggests that interaction mechanism between subsidiary and headquarter is the best solution to launch a new product to the local market.